2020
DOI: 10.1039/d0tc03421e
|View full text |Cite
|
Sign up to set email alerts
|

Structure-induced optoelectronic properties of phenothiazine-based materials

Abstract: Phenothiazine (PTZ)-based materials have recently received considerable interest owing to their intriguing optoelectronic properties, low-cost, versatility of functionalization, and commercial availability. The advent of molecular engineering concepts in π-conjugated organic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 109 publications
(177 reference statements)
0
55
0
Order By: Relevance
“…This value for the Br-2EPT is in good agreement with those reported previously. [35] In addition, numerous reports have indicated that the sulphur can passivate interfacial trap states, suppress charge recombination and inhibit ion migration, thereby enhancing the stability and performance of PSCs. [36,37] Subsequently, electron-withdrawing Br groups were introduced as substituents in the phenothiazine moiety to better align the energy levels with the perovskite materials, by modifying the work function (WF) of the transparent conductive oxide (TCO) substrate through its permanent dipole moment (vide infra).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This value for the Br-2EPT is in good agreement with those reported previously. [35] In addition, numerous reports have indicated that the sulphur can passivate interfacial trap states, suppress charge recombination and inhibit ion migration, thereby enhancing the stability and performance of PSCs. [36,37] Subsequently, electron-withdrawing Br groups were introduced as substituents in the phenothiazine moiety to better align the energy levels with the perovskite materials, by modifying the work function (WF) of the transparent conductive oxide (TCO) substrate through its permanent dipole moment (vide infra).…”
Section: Resultsmentioning
confidence: 99%
“…This value for the Br‐2EPT is in good agreement with those reported previously. [ 35 ] In addition, numerous reports have indicated that the sulphur can passivate interfacial trap states, suppress charge recombination and inhibit ion migration, thereby enhancing the stability and performance of PSCs. [ 36,37 ]…”
Section: Resultsmentioning
confidence: 99%
“…Phenothiazine is often used as a donor substituent that adopts a butterfly-type conformation in various optoelectronic materials. [39] (Di)phenothiazinedibenzothiophene-S,S-dioxides 17 a and 18 a exhibited prompt fluorescence and thermally activated delayed fluorescence (TADF) (Figure 8). [40] In contrast, the corresponding 1-methylphenothiazine-substituted derivatives 17 b and 18 b did not exhibit TADF, displaying RTP instead, when the luminophores were dispersed in Zeonex film.…”
Section: Diarylsulfonesmentioning
confidence: 99%
“…Phenothiazine is often used as a donor substituent that adopts a butterfly‐type conformation in various optoelectronic materials [39] . (Di)phenothiazinedibenzothiophene‐ S , S ‐dioxides 17 a and 18 a exhibited prompt fluorescence and thermally activated delayed fluorescence (TADF) (Figure 8).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] One area in which D-p-A systems have been immensely explored is dye sensitized solar cells (DSSCs). [5][6][7][8] Over the last two decades, DSSCs have also captured the interest of green energy scientists as a means of cost-effective solar energy conversion. [9][10][11] Since the pioneering work of Gra ¨tzel and co-workers, extensive endeavors have been made to increase the power conversion efficiencies of DSSCs.…”
Section: Introductionmentioning
confidence: 99%